Cerebral Palsy (CP) Categories BC1, BC4, and BC5: The Impact of Eye-Hand Coordination Training on Boccia Ball Throwing Accuracy at the DKI Jakarta Student Boccia Club - Ibrahim, Wahyu Maulid; Hartono, Fajar Vidya; Mustara, Mustara Vidya (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2025)
Objectives: The purpose of this study is to ascertain how training in eye-hand coordination affects the accuracy of boccia ball throws in BC1, BC4, and BC5 categories. This study specifically aims to ascertain the extent to which training in eye-hand synchronization improves ball throw accuracy. Material and Methods : Using an experimental approach and a one-group pre-test and post-test design, this study was carried out between November and December of 2024. Eleven individuals made up the research sample. An initial test prior to therapy and a final test following treatment were among the research tools. The t-test, which compares the computed t-value with the t-table at a significance level of 0.05, was the analysis method employed. Results: The average difference (M) = 2.54, standard deviation (SDD) = 1, and standard error of the mean difference (SEMD) = 0.32 are the findings of the first and final test computations. At a significance threshold of 0.05, additional computations reveal that the t-count value = 3.32 and the t-table value = 1.81. Conclusion: The alternative hypothesis (H₁) is accepted while the null hypothesis (H₀) is rejected since the t-count value is higher than the t-table. The accuracy of boccia ball throws in categories BC1, BC4, and BC5 at the DKI Jakarta Boccia Club is therefore impacted by eye-hand coordination training. To compare the efficacy of this training with alternative approaches, more study can be done by including a control group. Furthermore, a more thorough comprehension of how this training affects athlete performance can be obtained by analyzing the biomechanical components of boccia throwing techniques.